Thomas Jefferson on indigence in Spanish America the power of the Republican ideal - Vajda Zoltán (Universidad de Szeged, Departamento de Estudios Hispánicos Szeged, 2020)
As has been amply documented, Thomas Jefferson expressed a sincere interest in the peoples of Spanish America with the waning of colonial rule in the early nineteenth century. I argue in this paper that a substantial portion of his vision was comprised by implying Spanish American societies as ones defined through poverty. His understanding of indigence among peoples of the region was not simply confined to describing their economic condition, but was linked to a moral-political vision with the problem of independence as the major issue related economic poverty. I also contend, at the same time, that Jefferson in fact articulated his hope that Spanish American nations would be able to develop a republican structure of government, made possible by the special economic situation of the Western hemisphere, thus also implying the chance of tackling poverty there.
Keywords: Bölcsészettudományok; Történettudomány és régészet